The Role of Landscape Architecture in Sustainable Urban Development: Implementation of Universal Design - Nahdatunnisa; Fajar; Tahir, M. Arzal; Setiadi, Ahsan Hidayat (RUAS, 2024)
Landscape architecture significantly contributes to sustainable development by incorporating universal design principles in the design of public open spaces. The design of urban parks, green corridors, and public squares prioritizes ecological sustainability and accessibility. Universal design incorporates accessibility features like ramps, tactile paths, and safe materials, while also promoting ecological sustainability through the use of green infrastructure like catchment parks and bioswales. This case study takes place in a public area in Kendari. We gathered the data through observational and interview techniques. We utilize analytical and synthetic methods to understand requirements, capabilities, and obstacles while integrating ecological, social, and technical components into a cohesive design. The research findings consist of practical principles and recommendations for the implementation of universal design in landscape architecture, encompassing layouts that facilitate social interaction, the utilization of sustainable materials, and solutions for water management. This research demonstrates that universal design enhances inclusivity while offering ecological, social, and cultural advantages; therefore, it aids in the development of public places that are adaptable, inclusive, and promote urban sustainability.